How Do Literacy Teacher Educators Engage as Literacy Leaders? - Laurie A. Sharp; Marla Robertson; Rebekah E. Piper; Teresa Young; Roberta D. Raymond (The Advocate, 2019)
Literacy teacher educators play a pivotal role in developing future PreK-12 classroom teachers for the task of literacy leadership. However, little is known about literacy teacher educators and how they engage as literacy leaders. In the current study, we retrieved data from 132 literacy teacher educators and analyzed it descriptively using teacher educator identify as a theoretical lens. Findings revealed 15 different literacy leadership practices that represented five distinct groups. Among these groups, respondents demonstrated high and low levels of engagement with literacy leadership practices that pointed to important implications for administrators of teacher education programs.
Keywords: literacy leadership; literacy teacher education; literacy teacher educators; preservice teachers; teacher education